Foreign aid and emerging powers : Asian perspectives on official development assistance - Watson, Iain, 1972- (New York, NY : Routledge, Taylor & Francis Group, 2014)
'Current debates on emerging powers as foreign aid donors often fail to examine the myriad geopolitical, geoeconomic and geocultural tensions that influence policies of Official Development Assistance (ODA). This book advocates a regional geopolitical approach to explaining donor-donor relationships and provides a multidisciplinary critical assessment of the contemporary debates on emerging powers and foreign aid, bringing together economic and geopolitical approaches in the light of the 2015 completion of the Millennium Development Goals (MDGs). Moving away from established debates assessing the advantages and disadvantages of foreign aid, this book challenges the current geopolitical assumptions of the emerging powers concerning issues such as'south-south' solidarity, shared development experience and'multipolarity'. It analyses how donor governments'sell' aid to recipients through enabling different cultural assumptions and soft power narratives of national identity and provides empirical evidence on agendas such as aid effectiveness, aid for trade, public-private partnerships, and green growth aid. The book examines the role of, and relationships between, the leading traditional and emerging power Asian donors specifically, and explores the different and contested perspectives and patterns of ODA policy through an alternative account of emerging power foreign aid to leading African and Asian recipients.This book provides a valuable resource for postgraduate students and practitioners across disciplines such as development economics and geopolitics of development, uniquely approaching the debate from the perspective of emerging powers and donors.'--
'This book provides a multidisciplinary assessment of the contemporary debates on foreign aid. Covering the key debates of foreign aid, the book brings together economic and geopolitical approaches to the issues in the light of the 2015 completion of the Millennium Development Goals. The book argues that the foreign aid debate and agenda-setting is impacted upon by the new geopolitical role of emerging power donors and in particular those donors who themselves once received foreign aid'--
Includes bibliographical references and index.
Keywords: Economic assistance, Chinese; Economic assistance, Indian; Economic assistance, Russian; Economic assistance, Japanese